ZNF582 hypermethylation as a prognostic biomarker for malignant transformation of oral lesions. (1st July 2021) - Juan, Yi‐Chen; Su, Yee‐Fun; Bai, Chyi‐Huey; Fan, Yen‐Chun; Kuo, Tzu‐Tung; Ko, Hui‐Hsin; Peng, Hsin‐Hui; Chiang, Chun‐Pin; Fwu, Chyng‐Wen; Cheng, Shih‐Jung
Abstract: Objectives: This hospital‐based cohort study evaluated whether ZNF582 and PAX1 methylation levels at baseline can be used as biomarkers to identify lesions with a high potential for malignant transformation in patients with normal mucosa and oral potentially malignant disorders. Patients and methods: We recruited 171 adult patients with normal mucosa and oral potentially malignant disorders in 2012–2014. They were followed until 2017. Outcomes, including advanced histopathological findings and oral cancer occurrence, were obtained from medical charts, the Taiwan Cancer Registry, and cause‐of‐death data. Kaplan–Meier analysis and Cox proportional hazards regression models were used to examine the association of ZNF582 and PAX1 methylation levels at baseline with subsequent outcome occurrences. Results: After 260, 192 days of follow‐up, 11 cases of oral cancer and 4 cases of advanced histopathological progression occurred. Patients with higher ZNF582 and PAX1 methylation levels at baseline had a higher incidence of disease progression. After adjustment for all studied factors using Cox proportional hazards regression models, ZNF582 m level (adjusted hazard ratio, 11.41; 95% CI, 2.05–63.36; p = 0.005) was the only significant and independent predictor of disease progression. Conclusions: ZNF582 hypermethylation can be an effective and noninvasive biomarker for identifying oral lesions with a high potential for malignant transformation.